2022
DOI: 10.1111/all.15515
|View full text |Cite
|
Sign up to set email alerts
|

circS100A11 enhances M2a macrophage activation and lung inflammation in children with asthma

Abstract: Background Dysregulation of circRNAs is associated with a variety of human diseases; however, its role in childhood asthma is undefined. Methods The differential expression profiles of circRNAs were analyzed by microarray. The effects and mechanisms by which circRNAs influence macrophage activation were detected by quantitative real‐time PCR, RNA immunoprecipitation assay, and chromatin immunoprecipitation assay, among others. The roles of circRNA and its host gene in asthma were tested in a cockroach allergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…circS100A11 was dominantly expressed in monocytes and significantly upregulated in children with asthma, reasonably for the M2 macrophage activation. Mechanistically, circS100A11 promoted S100A11 translation, which liberated SP3 from nucleolin and increased STAT6 expression ( Liang et al, 2023 ). Similarily, circPWWP2A could adsorb miR-223–3p to regulate NLRP3 after silica stimulation in pulmonary fibrosis ( Hou et al, 2023 ), and hsa_circ_0006916 was upregulated in pulmonary fibrosis, associated with the high expression level of M2 molecule TGF-β1, playing an important role in the activation of M1-M2 polarization ( Wu et al, 2023 ).…”
Section: Circrnas In Lung Treatment and Repairmentioning
confidence: 99%
“…circS100A11 was dominantly expressed in monocytes and significantly upregulated in children with asthma, reasonably for the M2 macrophage activation. Mechanistically, circS100A11 promoted S100A11 translation, which liberated SP3 from nucleolin and increased STAT6 expression ( Liang et al, 2023 ). Similarily, circPWWP2A could adsorb miR-223–3p to regulate NLRP3 after silica stimulation in pulmonary fibrosis ( Hou et al, 2023 ), and hsa_circ_0006916 was upregulated in pulmonary fibrosis, associated with the high expression level of M2 molecule TGF-β1, playing an important role in the activation of M1-M2 polarization ( Wu et al, 2023 ).…”
Section: Circrnas In Lung Treatment and Repairmentioning
confidence: 99%
“…The authors showed that these allergen molecules can be used in component‐resolved diagnosis or spiked into the extract to improve diagnostic efficacy 15 . In terms of allergic disease treatments, especially asthma, more recently Liang and colleagues have indicated that circS100A11 and S100A11 promoted M2a macrophage activation and lung inflammation in a murine asthma model and children with asthma, suggesting M2a to be a potential therapeutic and diagnostic target in children with asthma 16 . Employing a murine asthma model, Sun and colleagues have demonstrated that Fedratinib‐incorporated nanoparticles can overcome the shortcomings of free Fedratinib to alleviate asthma by reducing the number of eosinophils and CD4 + T cells in the lung tissue of asthmatic animals 17 .…”
Section: Figurementioning
confidence: 99%
“…15 In terms of allergic disease treatments, especially asthma, more recently Liang and colleagues have indicated that circS100A11 and S100A11 promoted M2a macrophage activation and lung inflammation in a murine asthma model and children with asthma, suggesting M2a to be a potential therapeutic and diagnostic target in children with asthma. 16 Employing a murine asthma model, Sun and colleagues have demonstrated that Fedratinib-incorporated nanoparticles can overcome the shortcomings of free Fedratinib to alleviate asthma by reducing the number of eosinophils and CD4 + T cells in the lung tissue of asthmatic animals. 17 More recently, a multicenter prospective study by Gao and colleagues has suggested that in asthmatic pre-schoolers, standard childhood vaccinations to common respiratory pathogens, including Haemophilus influenzae, Streptococcus pneumoniae, and influenza, have beneficial effects on asthma control and may modulate immune responses relevant to asthma pathogenesis.…”
mentioning
confidence: 99%
“…A majority of dysregulated circRNAs have emerged as crucial regulators in cancer progression by modulating numerous cancer-associated molecules, thereby promoting tumorigenesis, suppressing tumor immunity, inducing angiogenesis, facilitating invasion and metastasis. Furthermore, circRNAs exhibit aberrant expression patterns in various diseases and govern disease progression encompassing cardiovascular diseases, autoimmune disorders, and inflammation [ 21 23 ] (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%